Taungya experiment for rehabilitation of burnt-over forest in East Kalimantan - Sutisna, M. (Center for International Forestry Research, 2001)
The objective of the forest rehabilitation study with taungya system was to find out optimum method, cash crop species, constraints, and how much this system benefits forest rehabilitation. It was carried out using red meranti (Shorea smithiana) and rubber (Hevea brasiliensis) as plantation trees, and rice (Oryza sativa), maize (Zea mays), soya bean (Glycine max) and cassava (Manihot esculenta) for intercropping. The research has shown that there are a number of constraints to the use of taungya in East Kalimantan for the rehabilitation of burnt, logged-over forest. The problems are a mix of technical, economic and social. It was found that the costs of establishing the taungya is comparable with that for establishment of industrial forest plantations but technical problems such as the lack of soil preparation, poor quality seed and inadequate fertiliser application techniques resulted in very low yields of the intercrops. This was exacerbated by protection problems and significant damage by birds and browsing animals further reduced yields. Some of these problems may be overcome by guarding the taungya fields and planting crops such as fibre producers which need less protection. However, unless the taungya system can be made economic and attractive to villagers it will be difficult to implement, especially in an area where there is no shortage of land close to the villages.